The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsanm.1c00813
|View full text |Cite
|
Sign up to set email alerts
|

Polyniobate Nanothreads for Decomposition of the Nerve Agent Simulant Dimethyl Chlorophosphate

Abstract: The nanoscale one-dimensional polymeric polyniobate K12[Ti2O2]­[SiNb12O40]·22H2O (KSiNb) rapidly hydrolyzes the gaseous organophosphorus nerve agent simulant dimethyl chlorophosphate (DMCP). A multimodal approach combining X-ray, IR and Raman spectroscopies and computation reveals that this reaction, involving the initial nucleophilic attack of polyoxometalate (POM) oxygen at phosphorus, is greatly modulated by the polyniobate counterions: the most negative and nucleophilic oxygen atoms in KSiNb, the Ti–O–Ti a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…9 Pure and high concentrations of H 2 O 2 , however, are unstable and can readily oxidize organic material or decompose in the presence of light. 11,12 Several strategies have been developed and show great promise to circumvent the need for liquid-based decontaminants, notably metal oxides, 2,13,14 metal-organic frameworks, 15,16 polyoxometalates, 17 and reactive polymers. 18,19 However, it would be advantageous to be able to deliver H 2 O 2 in a nonliquid form that retains its efficacy to decontaminate CWA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Pure and high concentrations of H 2 O 2 , however, are unstable and can readily oxidize organic material or decompose in the presence of light. 11,12 Several strategies have been developed and show great promise to circumvent the need for liquid-based decontaminants, notably metal oxides, 2,13,14 metal-organic frameworks, 15,16 polyoxometalates, 17 and reactive polymers. 18,19 However, it would be advantageous to be able to deliver H 2 O 2 in a nonliquid form that retains its efficacy to decontaminate CWA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Earlier work has demonstrated the benefits of using aqueous forms of H 2 O 2 for the decontamination of HD that circumvent more conventional yet corrosive methods such as bleach . Pure and high concentrations of H 2 O 2 , however, are unstable and can readily oxidize organic material or decompose in the presence of light. , Several strategies have been developed and show great promise to circumvent the need for liquid-based decontaminants, notably metal oxides, ,, metal-organic frameworks, , polyoxometalates, and reactive polymers. , However, it would be advantageous to be able to deliver H 2 O 2 in a nonliquid form that retains its efficacy to decontaminate CWA. Stable solid complexes of H 2 O 2 , such as urea-H 2 O 2 , can overcome this limitation, but the complex itself can become unstable at temperatures higher than 40 °C, thus limiting its shelf life …”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] In addition, PONbs have basic surface oxygen atoms, [37][38][39] which can accelerate the hydrolysis of nerve agents. 40,41 Nyman et al initially demonstrated the hydrolysis of Sarin and Soman using homogeneous Lindqvist [Nb 6 O 19 ] 8− . 42 Then, Hill and Zheng reported that Keggin-type PONb, K 12 [Ti 2 O 2 ][XNb 12 O 40 ] (X = Ge or Si), and copper-containing PONb, H 2 Li 5 Na 5 K 5 [Cu(en) 2 ] 7 [Nb 47 O 128 (OH) 6 (CO 3 ) 2 ]•20H 2 O (en = ethylenediamine), as solid bases can catalyze the hydrolysis of nerve agent simulants, but their sluggish hydrolysis kinetics leaves much room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Starting in 2002, Nb-POM chemistry has mostly relied on the blind and uninformed process of hydrothermal synthesis for compositional and topological diversification. Yet applications in nerve agent degradation, H 2 evolution, and other catalytic reactions arose from the increased diversification of Nb-POM chemistry. Reviewed here, the manipulations of Nb 10 to diversify the form and function of Nb-POMs are conducive to studying reaction pathways and embody the principles of sustainable chemistry. All experiments are performed in water at mild pH with minimal electrolytes and at room temperature.…”
Section: Introductionmentioning
confidence: 99%